Concept of Assessment Model for The Elements of Safety Culture In An Organization - Tomasz EWERTOWSKI; Kinga CZERNIAK (Communications of International Proceedings, 2021)
Safety in an organization consists of many components, which may be analyzed and assessed to a greater or lesser extent. Safety culture is a relatively new term, but increasingly used in the context of shaping safe behaviors and limiting accident rate in companies and other organizations. It is influenced by many factors, and the term may be defined and understood in many ways. Despite great amount of definitions and described factors shaping mentioned notion, there are still no regulations and standards concerning methods and tools for analysis the level of safety culture. Subject of this article focuses on the safety culture, the aspects defining it and possible methods of assessment of its level in an organization. In the first part, the authors are giving definitions of terms concerning organizational culture and safety culture, and are also presenting the differences between safety culture and safety climate. Furthermore, based on selected definitions of safety culture, a list of the most significant factors that constitute this phenomenon has been compiled. Based on the identified factors, a model, which can be used for the asssessment of safety culture, has been created; the model underwent initial verification by means of a questionnaire conducted among the employees of a selected organization. In the final part of the article, the results of the conducted survey and conclusions drawn from it have been presented. The results of the analyses allow managers to find out what aspects need to be taken into account to increase the safety culture of an organization.
Keywords: Safety culture; safety management; safety climate; occupational health and safety